1998
DOI: 10.1016/s0009-9236(98)90106-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and the pharmacodynamic action of midazolam in young and elderly patients undergoing tooth extraction*

Abstract: Elderly patients are more sensitive to the sedative action of midazolam than young patients, and the sensitivity is caused by age-dependent pharmacodynamic alterations. The age-adjusted doses used are both effective (for sedative amnesia) and safe (in terms of arterial oxygen saturation, heart rate, and blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
30
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 46 publications
(16 reference statements)
10
30
0
2
Order By: Relevance
“…The same results were obtained with regards to gender (P>0.05). These data suggest that midazolam pharmacokinetics in Chinese after oral administration are unaffected by either age or gender, and this conclusion is consistent with studies of Caucasian subjects [34][35][36][37] . As an oral hypnotic, midazolam has been in the market for many years in China; however, there have been few pharmacokinetic studies [25][26][27] , and there is significant inter-study variability (Table 5).…”
Section: Midazolam Pharmacokinetics In Chinese After Oral Adminis Trasupporting
confidence: 88%
See 1 more Smart Citation
“…The same results were obtained with regards to gender (P>0.05). These data suggest that midazolam pharmacokinetics in Chinese after oral administration are unaffected by either age or gender, and this conclusion is consistent with studies of Caucasian subjects [34][35][36][37] . As an oral hypnotic, midazolam has been in the market for many years in China; however, there have been few pharmacokinetic studies [25][26][27] , and there is significant inter-study variability (Table 5).…”
Section: Midazolam Pharmacokinetics In Chinese After Oral Adminis Trasupporting
confidence: 88%
“…Investigation of the effects on midazolam pharmacokinetics using the PBPK model Previous studies in Caucasians demonstrated that the pharmacokinetics of midazolam were unaffected by age [34][35][36][37] ; however, this topic has never been examined in Chinese. In this study, the verified PBPK model was used to investigate the effects of age on midazolam pharmacokinetics in Chinese from a physiological perspective.…”
Section: Midazolam Pbpk Modelingmentioning
confidence: 99%
“…observée dans d'autres études cliniques [27], puis en chirurgie orale [28], mais il n'y a pas eu d'analyses complémentaires. Ainsi l'administration de midazolam doit être guidée par l'effet pharmacologique, et non pas par un schéma posologique strictement basé sur le poids.…”
Section: Variabilité Interindividuelleunclassified
“…D'autres études [28,36,[45][46][47] ont évalué la variation de la saturation en oxygène dans le cadre du suivi des constantes vitales. Elles confirment le fait que si l'on observe une diminution de la saturation en oxygène après l'administration, elle est cependant de courte durée et sans conséquence clinique.…”
Section: Effets Sur Les Fonctions Autonomesunclassified
“…Such factors include advanced age, hepatic or renal disease, cigarette smoking, chronic benzodiazepine administration, and coadministration of ethanol or other centrally acting compounds. [10][11][12] Therefore, our aim was to clarify the relevance of pharmacokinetic and pharmacodynamic factors to cognitive impairment after gastrointestinal endoscopy under diazepam.…”
Section: Introductionmentioning
confidence: 99%